Improvement of Hardness of Hydroxyapatite by the Addition of Silica from Tin Tailings - Fitri Afriani; Evi J; Zaitun; Yuant Tiandho (Journal of Engineering and Scientific Research, 2020)
The application of bone scaffolding in bone therapy is an alternative solution developed in bone tissue engineering technology to avoid bone donors' scarcity. The main requirement for a material that can be used as a scaffold is that it is biocompatible. Hydroxyapatite is a calcium phosphate ceramic that is often used as the primary material for scaffolding because it has good biocompatibility properties. However, like most ceramics, hydroxyapatite has low mechanical properties. In this study, we synthesized hydroxyapatite from cockleshell waste. To improve hydroxyapatite's mechanical properties (hardness), we added silica from tin tailings to hydroxyapatite. Through the analysis of the x-ray diffraction (XRD) pattern, it was found that hydroxyapatite was successfully synthesized from cockleshell using the co-precipitation method. Analysis of the diffraction pattern of tin tailings also shows that most of the crystals comprising tin tailings sand are silica in the ?-quartz phase. The addition of silica to hydroxyapatite followed by compaction and sintering at a temperature of 800 ? did not produce a new crystal phase. The addition still has a diffraction pattern consisting of a combined XRD pattern of hydroxyapatite and silica. Based on the hardness test using the Vickers hardness method, it is known that the addition of silica can increase the hardness of hydroxyapatite.